Taxonomic studies on smut fungi from North-Eastern India - D.K. AGARWAL, M.K. BAG and (Indian Phytopathology, 2002)
Four New species of the genus Sporisorium and one of Ustilago are described and illustrated for the first time from North-Eastern parts of India on grasses. These are S. agropyri Sp. novo on Agropyron strigosum L., S. assamensis Sp. Nov. on Digitaria sp., S. leersiae Sp. novo on Leersia hexandra Swartz. and S. martinae Sp. novo on Cymbopogon martini (Roxb.) Wats. and Ustilago darjeelingensis Sp. novo on Setaria sp. Cintractia limitata on Cyperus rotundus (matrix nova) is reported for the first time from India. Three other smut fungi viz., Cintractia axicola on Cyperus scariossus (matrix nova). Farysia americana on Carex maculata (matrix nova) and Moesziomyces bullatus on Panicum miliaceam (matrix nova) are reported for the first time from North-East India. Sporisorium setaricolum is proposed as Combination novum on Setaria sp.